Current Status of Oligonucleotide-Based Protein Degraders - Po-Chang Shih; Miyako Naganuma; Yosuke Demizu; Mikihiko Naito (MDPI AG, 2023)
Transcription factors (TFs) and RNA-binding proteins (RBPs) have long been considered undruggable, mainly because they lack ligand-binding sites and are equipped with flat and narrow protein surfaces. Protein-specific oligonucleotides have been harnessed to target these proteins with some satisfactory preclinical results. The emerging proteolysis-targeting chimera (PROTAC) technology is no exception, utilizing protein-specific oligonucleotides as warheads to target TFs and RBPs. In addition, proteolysis by proteases is another type of protein degradation. In this review article, we discuss the current status of oligonucleotide-based protein degraders that are dependent either on the ubiquitin-proteasome system or a protease, providing a reference for the future development of degraders.